Characterization of enteropathogenic and Shiga toxin-producing Escherichia coli in cattle and deer in a shared agroecosystem - Singh, Pallavi; Sha, Qiong; Lacher, David W.; Del Valle, Jacquelyn; Mosci, Rebekah E.; Moore, Jennifer A.; Scribner, Kim T.; Manning, Shannon D. (Frontiers in Cellular and Infection Microbiology, 2015)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne pathogen. Cattle are suggested to be an important reservoir for STEC; however, these pathogens have also been isolated from other livestock and wildlife. In this study we sought to investigate transmission of STEC, enterohemorrhagic E. coli (EHEC) and enteropathogenic E. coli (EPEC) between cattle and white-tailed deer in a shared agroecosystem. Cattle feces were collected from 100 animals in a Michigan dairy farm in July 2012, while 163 deer fecal samples were collected during two sampling periods (March and June). The locations of deer fecal pellets were recorded via geographic information system mapping and microsatellite multi-locus genotyping was used to link the fecal samples to individual deer at both time points. Following subculture to sorbitol MacConkey agar and STEC CHROMagar, the pathogens were characterized by serotyping, stx profiling, and PCR-based fingerprinting; multilocus sequence typing (MLST) was performed on a subset. STEC and EHEC were cultured from 12 to 16% of cattle, respectively, and EPEC was found in 36%. Deer were significantly less likely to have a pathogen in March vs. June where the frequency of STEC, EHEC, and EPEC was 1, 6, and 22%, respectively. PCR fingerprinting and MLST clustered the cattle- and deer-derived strains together in a phylogenetic tree. Two STEC strains recovered from both animal species shared MLST and fingerprinting profiles, thereby providing evidence of interspecies transmission and highlighting the importance of wildlife species in pathogen shedding dynamics and persistence in the environment and cattle herds.